2021
DOI: 10.1038/s41598-021-01885-0
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation of chronic HBV and HCV patients seeking first time specialist care in Spain: a 2-year registry review

Abstract: Chronic viral hepatitis infection affects an estimated 325 million people globally. People who initiate treatment after significant disease progression face increased risk of severe liver complications and death. Data are scarce on the characteristics and risk factors of people who present late to care in Spain and globally. Data were collected from January 2018 to December 2019 to report late presentation (LP) to specialist care at 11 large university hospitals in Spain to assess related risk factors using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 25 publications
4
3
0
Order By: Relevance
“…Interestingly, in our experience, 22% of viraemic HCV patients had advanced liver disease (i.e., decompensated cirrhosis or hepatocellular carcinoma), highlighting the need for earlier diagnosis. Our findings confirm other research that underscores late diagnosis and presentation to specialist viral hepatitis care as an important issue within the healthcare system [ 20 ]. Additionally, HCV-related disease inflicts a huge economic and clinical burden, even as a result of HCV-related extrahepatic comorbidities [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in our experience, 22% of viraemic HCV patients had advanced liver disease (i.e., decompensated cirrhosis or hepatocellular carcinoma), highlighting the need for earlier diagnosis. Our findings confirm other research that underscores late diagnosis and presentation to specialist viral hepatitis care as an important issue within the healthcare system [ 20 ]. Additionally, HCV-related disease inflicts a huge economic and clinical burden, even as a result of HCV-related extrahepatic comorbidities [ 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Patients with suboptimal diagnosis, that is, with a positive HCV antibody with unknown RNA, and those with active infection lost to follow-up, were considered a priority group to be linked to care in the microelimination plans 16 mainly because these patients have a high probability of active infection and are at risk of liver fibrosis progression 9 and late presentation. 17 It is important to emphasize that in our cohort of 13 years of testing, nearly one fourth of the patients with positive serology for HCV remained without full evaluation or treatment for a median of 7 years with positive HCV antibodies, which is consistent with other studies. 16 Some might think that these patients are lost to follow-up because they are likely to be difficult to treat; however, this group of patients is characterized as being young male without comorbidity, with a history of drug use, and having abnormal transaminases without previous specialist evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…Our study found a higher risk of LP clearly associated with increasing age, male gender, a history of alcohol overuse and lack of postprimary education. Overall, our findings echo the results of several studies for higher age and male gender and a history of alcohol overuse as risk factors for LP [18,[24][25][26][27]. Further risk factors found in other studies are being diagnosed longer than 2 years before referral, genotype 3, MSM [25] and suffering from diabetes [26].…”
Section: Discussionsupporting
confidence: 90%